Exploring the Isomeric Precursors of Olive Oil Major Secoiridoids: An Insight into Olive Leaves and Drupes by Liquid-Chromatography and Fourier-Transform Tandem Mass Spectrometry - Ramona Abbattista; Ilario Losito; Cosima Damiana Calvano; Tommaso R. I. Cataldi (Foods, 2021)
Secoiridoids play a key role in determining health benefits related to a regular consumption of extra-virgin olive oil (EVOO), in which they are generated from precursors of the same class naturally occurring in drupes and leaves of the olive (Olea europaea L.) plant. Here, reversed-phase liquid chromatography coupled to electrospray ionization and Fourier-transform single/tandem mass spectrometry (RPLC-ESI-FTMS and MS/MS) was employed for a structural elucidation of those precursors. The presence of three isoforms in both matrices was assessed for oleuropein ([M-H]− ion with m/z 539.1770) and was emphasized, for the first time, also for ligstroside (m/z 523.1821) and for the demethylated counterparts of the two compounds (m/z 525.1614 and 509.1665, respectively). However, only the prevailing isoform included an exocyclic double bond between carbon atoms C8 and C9, typical of oleuropein and ligstroside; the remaining, less abundant, isoforms included a C=C bond between C8 and C10. The same structural difference was also observed between secoiridoids named elenolic acid glucoside and secoxyloganin (m/z 403.1246). This study strengthens the hypothesis that secoiridoids including a C8=C10 bond, recently recognized as relevant species in EVOO extracts, arise mainly from specific enzymatic/chemical transformations occurring on major oleuropein/ligstroside-like precursors during EVOO production, rather than from precursors having that structural feature.